Inside the Danger Zone : the U.S. Military in the Persian Gulf, 1987-1988. - Wise, Harold Lee (Naval Institute Press, 2013)
From the Iraqi attack on the USS Stark to Iranian mine fields to Revolutionary Guard gunboats, the 1987-88 Persian Gulf was a place of shadowy danger for U.S. Navy ships assigned to protect oil tankers during the Iran-Iraq War. A low-profile escort mission quickly became an international test of wills between the United States and Iran. The conflict escalated to involve secret missions and special operations until finally the United States and Iran engaged in open combat, most notably during Operation Praying Mantis in April 1988, the world's largest sea-air battle since World War II.